Intravital imaging of vascular anomalies and extracellular matrix remodeling in orthotopic pancreatic tumors. Issue 8 (23rd November 2019) - Bochner, Filip; Mohan, Vishnu; Zinger, Assaf; Golani, Ofra; Schroeder, Avi; Sagi, Irit; Neeman, Michal
Abstract : Pancreatic cancers, both adenocarcinomas and endocrine tumors are characterized by varying levels of aberrant angiogenesis and fibrotic microenvironment. The difficulty to deliver drugs and treat the disease has been attributed in part to the vascular architecture and tissue/ECM density. Here we present longitudinal three‐dimensional intravital imaging of vascular and tumor microenvironment remodeling in spontaneous transgenic tumors (RIP1‐Tag2 insulinomas) and orthotopically injected tumors (KPC adenocarcinomas). Analysis of the data acquired in insulinomas revealed major differences in tumor blood vessel branching, fraction volume, number of branch points segments, vessel straightness and length compared to the normal tissue. The aggressive adenocarcinoma presented widespread peritumoral vascular remodeling and heterogeneous vascular distribution. Longitudinal imaging was used to acquire sequential vascular remodeling data during tumor progression. This work demonstrates the potential for using a pancreatic intravital imaging window for direct visualization of the tumor heterogenic microenvironments during tumor progression. Abstract : What's new? In pancreatic cancer, the difficulty to deliver therapeutic drugs has been attributed partly to the tumor vascular architecture and tissue/extracellular matrix density. Here, the authors present a novel method for longitudinal intravital imaging of preclinical models of pancreatic cancer that enables direct visualization of blood vessels remodeling and quantification of vascular parameters. The results provide information on blood vessel diameter, volume, length, branching, and straightness in spontaneous transgenic tumors and on vessel volume and heterogeneity in syngeneic fluorescent orthotopically‐injected adenocarcinomas. The work provides new monitoring tools together with quantifiable architectural features and potential biomarkers of vascular abnormalities in pancreatic cancer.